Peran Triangulasi dalam Meningkatkan Kredibilitas Penelitian Kualitatif pada Kajian Pendidikan Islam Kontemporer - Rumina (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2026)
Qualitative research in contemporary Islamic education studies frequently encounters methodological challenges related to the validity and credibility of research findings. This study aims to analyze the role of triangulation as a verification strategy for enhancing data trustworthiness in qualitative research within the field of Islamic education. Employing a meta-synthesis approach to twenty-eight qualitative studies published between 2015 and 2024, this research examines the application of four forms of triangulation—source, methodological, investigator, and theoretical triangulation—within the context of Islamic education studies across educational institutions in Indonesia and Malaysia. The findings indicate that methodological and source triangulation are the most widely employed strategies; however, theoretical triangulation significantly enhances the depth of interpretation in hermeneutic and text-based studies. The study also identifies a critical gap in the implementation of investigator triangulation due to institutional resource limitations. The practical implications of this research include the recommendation of an integrative triangulation framework that can be adopted by Islamic education researchers, particularly in the contexts of curriculum development, pedagogical interpretation, and Islamic values-based character education. This study contributes to the discourse on qualitative research methodology in Islamic studies by affirming that credibility is not merely a technical procedure but an epistemological commitment that must be embedded throughout the entire research design